Analisis SWOT Terhadap Kebijakan Pajak Digital di Indonesia - Istiarti Primadini; Gunadi Gunadi (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2023)
This study aims to analyze the potential success of digital transaction tax collection policies. The method used is a descriptive research that has a qualitative approach (data comes from literature). Data analysis using the SWOT method (Strength, Weakness, Opportunities, Threats). The results of the research based on the calculations of the IFAS and EFAS matrices as well as cartesius diagram images, it can be analyzed that the strategy used by the Government is a survival strategy (WO/Weakness Opportunity Strategy) in supporting the success of digital taxation policies in Indonesia. WO strategy is an analysis with a strategy of managing or managing available opportunities to minimize or eliminate existing weaknesses or limitations. The government's WO strategy is that DGT's access to data search for foreign business actors is hampered and it is difficult to track foreign business actor's tax compliance. By maximizing international information exchange facilities, this obstacle can be overcome. Weak monitoring and law enforcement for non-compliance with VAT collectors, the government can learn from international agreement forums organized by OECD and G-20 countries and the exchange of international information.